2017
DOI: 10.1016/j.scitotenv.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon dioxide emissions from a rubber plantation on tropical peat

Abstract: Land-use change in tropical peatland potentially results in a large amount of carbon dioxide (CO) emissions owing to drainage, which lowers groundwater level (GWL) and consequently enhances oxidative peat decomposition. However, field information on carbon balance is lacking for rubber plantations, which are expanding into Indonesia's peatlands. To assess soil CO emissions from an eight-year-old rubber plantation established on peat after compaction, soil CO efflux was measured monthly using a closed chamber s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
7
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 43 publications
7
59
7
4
Order By: Relevance
“…3d and 4e). Wakhid et al (2017) showed a clear relationship between GWL and PD in a nearby rubber plantation established using heavy machinery after peat compaction; their study site was located 25 km from ours. In their results, the CO2 efflux from PD increased linearly with decreasing GWL (r 2 = 0.94-0.98).…”
Section: Factors Affecting Oxidative Peat Decompositionmentioning
confidence: 80%
See 2 more Smart Citations
“…3d and 4e). Wakhid et al (2017) showed a clear relationship between GWL and PD in a nearby rubber plantation established using heavy machinery after peat compaction; their study site was located 25 km from ours. In their results, the CO2 efflux from PD increased linearly with decreasing GWL (r 2 = 0.94-0.98).…”
Section: Factors Affecting Oxidative Peat Decompositionmentioning
confidence: 80%
“…Then, to understand how the environmental factors affects CO2 fluxes, we compared the results from different types of land use under the same geophysical conditions. Wakhid et al (2017) recently reported both PD and SR for compacted peat in a rubber plantation only 25 km from our observation sites, enabling us to compare our results with data from a plantation. Finally, seasonal variation and annual CO2 emissions were estimated using empirical models.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Part of this variation may reflect genuine differences in local contexts but variations in methods and associated biases cannot be excluded. While chamber-based estimates(Wakhid et al, 2017) require…”
mentioning
confidence: 99%
“…This recommendation byWösten et al (2008) has been used as a generic policy standard in Indonesia. The rate of CO 2 emissions of large-scale plantations has been widely studied(Page et al, 2011a;Carlson et al, 2015;Sumarga et al, 2016;Wakhid et al, 2017) but little is yet known of the subsidence and emission dynamics in the specific context of smallholder mosaic landscapes. Nonetheless, mandated groundwater levels for rewetted peat landscapes are applied to smallholder landscapes as well as plantations.…”
mentioning
confidence: 99%